2018
DOI: 10.3390/en11102541
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations of the Interactions between Hydraulic and Natural Fractures in Shale Formations

Abstract: Natural fractures (NFs) have been recognized as the dominant factors that increase hydraulic fracture complexity and reservoir productivity. However, the interactions between hydraulic and natural fractures are far from being fully understood. In this study, a two-dimensional numerical model based on the displacement discontinuity method (DDM) has been developed and used to investigate the interaction between hydraulic and pre-existing natural fractures. The inelastic deformation, e.g., stick, slip and separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Rocks are complex in multiscale with heterogeneous structures, which makes prediction models for geomechanical properties challenging [1][2][3][4][5][6]. An emerging necessity to link microscale to macroscale properties has led researchers to take efforts to propose multiscale models of poromechanical behaviors, for different rock types [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Rocks are complex in multiscale with heterogeneous structures, which makes prediction models for geomechanical properties challenging [1][2][3][4][5][6]. An emerging necessity to link microscale to macroscale properties has led researchers to take efforts to propose multiscale models of poromechanical behaviors, for different rock types [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Natural fractures play a significant role in the creation of fracture networks [24]. Hydraulic fracture growth depends on the shear slip of natural fractures or Processes 2022, 10, 2604 2 of 18 bedding planes with different cement strengths, which is documented by both numerical results and tri-axial hydraulic fracturing experiments [25,26]. A study demonstrates that after intersecting hydraulic fractures, failure modes within cemented natural fractures may change from tensile regime to mixed-mode or shear regime in heterogeneous reservoirs [27].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the displacement discontinuity method (DDM), a two-dimensional numerical model has been developed and used to investigate the interaction between hydraulic and pre-existing natural fractures. Research has shown that the cemented strength of the NF has an important influence on the interaction mechanism [7]. In the fracturing experiment, the anisotropy of shale plays an important role in the mechanical behavior and fracture propagation.…”
Section: Introductionmentioning
confidence: 99%